Efficient degenerate middle infrared ZGP-OPO pumped by an electro-optically Q-switched Tm:YAP laser - Dai, Wantian; Ding, Yu; Liu, Tongyu; Zhao, Yuwei; Gao, Jia; Zhao, Chen (Frontiers in Physics, 2024)
In this paper, we demonstrated an efficient degenerate middle infrared (mid-IR) ZGP-OPO that is pumped by an electro-optically Q-switched diode-pumped Tm:YAP laser. The Tm:YAP laser, operating at a repetition rate of 1 kHz, produced a peak pulse energy of 9.66 mJ at 1.94 μm and a minimum pulse width of 25 ns. Utilizing the Tm:YAP laser as the pump source, a peak average output power of 3.14 W at 3.88 μm was achieved in the degenerate ZGP-OPO with an incident Tm power of 9.4 W, resulting in a slope efficiency of 62.7% and an optical conversion efficiency of 33.4%. The minimum pulse width was measured at 21 ns, leading to a peak power of 149.5 kW. Additionally, the beam quality factor of the degenerate mid-IR ZGP-OPO was evaluated to be approximately 2.7 at the maximum output power level.